Implementasi Smart City di Kota Tangerang Selatan Banten - Sapraji Sapraji (UIN Syarif Hidayatullah Jakarta, 2023)
Abstract. This research discusses the implementation of the Smart City policy in South Tangerang City, Banten, Indonesia as a response to regional autonomy demands and the complexity of urban issues. As an innovative concept, Tangsel Smart City focuses on providing solutions to community problems through the application of Information and Communication Technology (ICT). Through innovation and renewal, the South Tangerang City Government has successfully increased efficiency in public services, especially in licensing, taxation, and budgeting. This study is based on the Decree Number 134.43/Head.220-Legal/2017 and Memorandum of Understanding between the Ministry of Communication and Information Technology and the Local Government of South Tangerang City. Although the implementation of Smart City in Tangsel has brought positive changes, there are challenges such as the lack of supporting application functions, suboptimal socialization, difficulties in inter-agency integration, and security issues. The aim of this research is to provide an in-depth overview of the Smart City policy implementation, evaluate its effectiveness, and identify opportunities and challenges. It is hoped that the results of this research contribute to both practical and theoretical understanding of Smart City implementation in autonomous regions, serve as a guide for further research, and encourage continuous efforts to improve the quality of public services through the Smart City concept. Keywords: Smart City, Policy Implementation, Regional Autonomy, South Tangerang City, Public Services, Regional Government Innovation, Online Licensing. Abstrak. Penelitian ini membahas implementasi kebijakan Smart City di Kota Tangerang Selatan, Banten, Indonesia sebagai respons terhadap tuntutan otonomi daerah dan kompleksitas masalah perkotaan. Sebagai konsep terobosan, Tangsel Smart City fokus pada solusi masalah masyarakat dengan penerapan Teknologi Informasi dan Komunikasi (TIK). Melalui inovasi dan pembaharuan, Pemerintah Kota Tangerang Selatan berhasil meningkatkan efisiensi dalam pelayanan publik, terutama dalam perizinan, perpajakan, dan penganggaran. Penelitian ini berdasarkan Kepwal Nomor 134.43/Kep.220-Huk/2017 dan Nota Kesepahaman antara Kementerian Komunikasi dan Informatika dengan Pemda Kota Tangerang Selatan. Meskipun implementasi Smart City di Tangsel telah membawa perubahan positif, terdapat kendala seperti minimnya fungsi aplikasi pendukung, sosialisasi yang kurang optimal, kesulitan integrasi antar-dinas, dan masalah keamanan. Penelitian ini bertujuan untuk memberikan gambaran mendalam tentang implementasi kebijakan Smart City, mengevaluasi efektivitasnya, serta mengidentifikasi peluang dan tantangan. Diharapkan hasil penelitian ini dapat memberikan kontribusi pada pemahaman praktis dan teoritis tentang penerapan Smart City di daerah otonom, menjadi panduan bagi penelitian lebih lanjut, dan mendorong upaya terus-menerus dalam meningkatkan kualitas layanan publik melalui konsep Smart City. Kata Kunci: Smart City, Implementasi Kebijakan, Otonomi Daerah, Kota Tangerang Selatan, Pelayanan Publik, Inovasi Pemerintah Daerah, Perizinan Online.